Flow Experience Pada Muslimah Pendaki Gunung - Sarah Afifah (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2019)
Muslim women who have feminine stereotypes: gentle, shy, preferring to stay at home with the phenomenon of Muslim climberswho are looking for challenges by climbing the mountain has now shifted to be more masculine. Mountain climbing is a masculine activity because it seeks challenges by climbing high-risk mountains. Mountain climbers experience flow experince which is a holistic sensation that is manifested when we take action with full involvement. This study uses a qualitative phenomenological method to understand the description of flow experince in Muslim women mountaineers. This research was conducted in the city of Yogyakarta with four participants. Data collected bysemi-structured interview techniques. This study found seven themes that emerged regarding flow experince in Muslim mountaineers, that is: 1) preparation was the main; 2) the purpose of climbing mountains is spirituality; 3) Muslim mountaineer women feel special; 4) Feeling at one with nature but staying focused; 5) get positive feedback 6) increase brotherhood 7) be able to evaluate yourself. The findings of this study are Muslim women climbers feel they can improve spirituality, self esteem, ukhuwah or brotherhood and feelings at one with nature but stay focused when they climb mountains.